Ovarian torsion in a 2-year-old girl: A case report - Anahita Haghjoo; Rahil Haghjoo; Marzieh Rahimipour (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: Ovarian torsion (adnexal torsion) is a rare event in pediatric patients which is primarily managed by pediatric general surgeons. Case presentation: This study presents a case of ovarian torsion in a 2-yr-old girl with a history of episodic lower abdominal pain, nausea, and vomiting for 2 days. Her physical examination was normal except for mild tenderness in the lower abdomen with no palpable mass. A color Doppler ultrasound was performed for further investigation, and an ovarian torsion was reported without sonographic signs of intussusception and acute appendicitis, so she underwent laparotomy. A relatively complete torsion was observed in the left ovarian pedicle. Initially, the left ovary and fallopian tube had a dark appearance, and 10-15% of the ovarian tissue was still normal. Detorsion of ovary was done and it was decided to preserve the ovary. After about 20 min, the color of ovary and fallopian tube returned to relatively normal, indicating normal blood flow. The patient was discharged 2 days later because a follow-up color Doppler ultrasound showed normal ovarian blood flow. Conclusion: The possibility of ovarian torsion must be considered in all female infants with suspicious abdominal pain.